Commercialisation of non-timber forest products: a reality check - Belcher, B.; Schreckenberg, Kate (2007)
This article challenges the pervasive view that commercialisation of non-timber forest products can (easily) achieve ecosystem and species conservation as well as improving livelihoods. Following a brief review of who and what is involved, it focuses on the main ecological and livelihood risks of unconsidered promotion of NTFP commercialisation, drawing on a wide range of case studies from around the world. It concludes with some recommendations, emphasising the lack of "magic-bullet" products, and the importance - among other things - of not ignoring national policy, taking an integrated view of the value chain, considering the implications of different production options, and improving both quality and quantity.